Taxonomic notes with update of records of Trigona (Dichrotrigona) Engel, 2021 (Hymenoptera: Apidae: Meliponini) - Ribeiro, Cristiano Feitosa; Nogueira, David Silva; Oliveira, Marcio Luiz de (EntomoBrasilis, 2024)
In this paper, we provide taxonomic notes for species of the Trigona (Dichrotrigona) Engel, 2021, with additional photographs. An identification key and a distribution map of the species of this subgenus is also provided here. We also update records of Trigona (Dichrotrigona) sesquipedalis Almeida, 1984 (Hymenoptera: Apidae: Meliponini) with the first records for the state of Roraima, Brazil.